Assessment of Patient Factors, Surgeons, and Surgeon Teams in Immediate Implant-Based Breast Reconstruction Outcomes. Issue 2 (February 2015) - Gfrerer, Lisa; Mattos, David; Mastroianni, Melissa; Weng, Qing Y.; Ricci, Joseph A.; Heath, Martha P.; Lin, Alex; Specht, Michelle C.; Haynes, Alex B.; Austen, William G.; Liao, Eric C.
<x xml:space="preserve">Abstract</x> Background: Outcome studies of immediate implant-based breast reconstruction have focused largely on patient factors, whereas the relative impact of the surgeon as a contributing variable is not known. As the procedure requires collaboration of both a surgical oncologist and a plastic surgeon, the effect of the surgeon team interaction can have a significant impact on outcome. This study examines outcomes in implant-based breast reconstruction and the association with patient characteristics, surgeon, and surgeon team familiarity. Methods: A retrospective review of 3142 consecutive implant-based breast reconstruction mastectomy procedures at one institution was performed. Infection and skin necrosis rates were measured. Predictors of outcomes were identified by unadjusted logistic regression followed by multivariate logistic regression. Surgeon teams were grouped according to number of cases performed together. Results: Patient characteristics remain the most important predictors for outcomes in implant-based breast reconstruction, with odds ratios above those of surgeon variables. The authors observed significant differences in the rate of skin necrosis between surgical oncologists with an approximately two-fold difference between surgeons with the highest and lowest rates. Surgeon teams that worked together on fewer than 150 procedures had higher rates of infection. Conclusions: Patient characteristics are the most important predictors for surgical outcomes in implant-based breast reconstruction, but surgeons and surgeon teams are also important variables. High-volume surgeon teams achieve lower rates of infection. This study highlights the need to examine modifiable risk factors associated with optimum implant-based breast reconstruction outcomes, which include patient and provider characteristics and the surgical team treating the patient. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, III.